Amyloid-Beta-Related Angiitis with Distinctive Neuro-Ophthalmologic Features. (4th July 2018) - Dumitrascu, Oana M.; Okazaki, Erin M.; Cobb, Steven H.; Zarka, Matthew A.; De Souza, Stephen A.; Kumar, Gyanendra; O'Carroll, Cumara B.
ABSTRACT: Amyloid beta-related angiitis (ABRA) is a subtype of cerebral amyloid angiopathy-related inflammation, with distinctive pathology and prognosis compared with cerebral amyloid angiopathy (CAA). On a spectrum of increasing severity, ABRA is considered to be in-between the less aggressive inflammatory-CAA and the more severe primary central nervous system (CNS) angiitis. Whereas retinal pathological changes were described in subjects with primary or secondary CNS angiitis, and non-inflammatory CAA, bilateral posterior pole superficial and peripapillary retinal hemorrhages have not been reported as initial signs in patients with pathology-confirmed ABRA, accompanying neurological spells and characteristic neuroimaging findings.